The Effect of Positive Perceptions and Ease of Use to Financial Technology Peer to Peer Lending Of MSMEs In The Era Of Digital Economy - Pratiwi, Arta Zahra; Ramaputra, Muhammad Galih (Proceeding International Conference on Information Technology and Business, 2023)
The purpose of this study is to analyze the positive perceptions of MSME (Micro, Small and Medium Enterprises) players towards Financial Technology Peer To Peer Lending services in the midst of the digital economy era. Researchers hypothesize that there is a positive relationship between the positive perception of MSMEs towards the use of peer to peer lending financial technology and the perceived ease of use of peer to peer lending financial technology has a positive effect on the level of adoption of this technology by MSMEs in the digital economy era. The research method used is quantitative with the approach of distributing questionnaires to respondents, using a sample of 75 respondents who are owners and managers of MSMEs. The analytical tools used are SPSS and Microsoft Excel software.Keywords— Financial Technlogy, Peer To Peer Lending, MSME, Positive Perception, Perceived Ease of Use